PERAN DEWAN KEAMANANPERSERIKATAN BANGSA-BANGSA DALAM PENYELESAIAN KASUS TINDAK PIDANA TERORISME ISIS (ISLAMIC STATE OF IRAQ AND SYRIA) - Fioleta Putri Fakhni; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Terrorism as a crime has expanded to cross country crime taking place in a country not only seen as the jurisdiction of a single the state but it can claimed including jurisdiction crimes more than one country.With progress then it could create conflicts jurisdiction that can interfere with intemational relations between countries in handle cases dangerous crimes. Isis ( islamic state of iraq and syria is an organization having the objective of establish the state islam.gerakan this the first time born in the middle eastern regions led by ashes two al-baghdadi.The purpose of campaign times this is conquer and uniting areas syria, iraq, egypt, lebanon, jordan, and israel of being a state unity under flag caliphate, an empire apply the law the faith in full in run the administration the state.This type of research can be classified in the type of normative research, because in this study the authors find data in books and legal journal of the problems studied. The nature of descriptive research with primary data sources, secondary data and tertiary data, while the population and sample are the parties in the cooperation agreement examined in this study. Data collection techniques are interviews and literature review.From the results of research problems there are two main things that can be concluded.First, International community on view of criminal acts of terrorism done isis had violated international law norms .Violation of human rights , imposition ideology and terror who break balance and peace .International law having the international community namely the state of being agreed that isis is a threat so that required resolusi-resolution at the security council pursue the united nations to crack down on terrorism movement isis, Second, The role of the un security council poured in resolution 2253 acting in a military fashion, and all kinds of a manner to remove terrorist group isis immediately, with the role of all member states the un security council and all state member the united nations and borders before controlled isis narrowed so as to make isis depressed.Keyword : Terrorist – ISIS – UN Security Council